C reactive protein to albumin ratio (CAR) as predictor of anastomotic leakage in colorectal surgery. (September 2021) - Paliogiannis, Panagiotis; Deidda, Simona; Maslyankov, Svilen; Paycheva, Tsvetelina; Farag, Ahmed; Mashhour, Abdrabou; Misiakos, Evangelos; Papakonstantinou, Dimitrios; Mik, Michal; Losinska, Joanna; Scognamillo, Fabrizio; Sanna, Fabio; et al.
Abstract: Background: Anastomotic leakage (AL) is one of the most severe complications in colorectal surgery. Currently, no predictive biomarkers of AL are available. The aim of this study was to investigate the role of C reactive protein (CRP) to albumin ratio (CAR) as a predictor of AL in patients undergoing elective surgery for colorectal cancer. Materials and Methods. Data on 1183 consecutive patients surgically treated for histologically proven colorectal cancer in the surgical units involved in the study were collected. Data included sex, age, BMI, ASA score, Charlson comorbidity index, localization, histology and stage of the disease, as well as blood tests including albumin and CRP at the 4th postoperative day. Differences in CAR between patients who developed AL and those who did not were analyzed, and the ability of CAR to predict AL was investigated with ROC analysis. Results. CAR was significantly higher in patients with AL in comparison to those without, at the 4th postoperative day. In ROC analysis CAR showed a good ability in detecting AL (AUC 0.825, 95%CI: 0, 786–0, 859), greater than those of CRP and albumin alone. CAR also showed a high ability in detecting postoperative deaths (AUC 0.750, 95% CI 0, 956–0, 987). These findings were confirmed in multivariate analysis including the most relevant risk factors for AL. Conclusion. Our study evidenced that CAR, an inexpensive and widely available laboratory biomarker, adequately predicts AL and death in patients who underwent elective surgery for colorectal cancer. Highlights: Anastomotic leakage is one of the most common and severe complications in oncological colorectal surgery. No biomarkers are currently available for the early detection of anastomotic leakage in colorectal surgery. Blood biomarkers like C reactive protein (CRP) and albumin have been proposed for the early detection of anastomotic leak. The C reactive protein to albumin ratio (CAR) performs better than CRP or albumin alone in predicting anastomotic leak.